2009
DOI: 10.1073/pnas.0902159106
|View full text |Cite
|
Sign up to set email alerts
|

Protein elastic network models and the ranges of cooperativity

Abstract: Elastic network models (ENMs) are entropic models that have demonstrated in many previous studies their abilities to capture overall the important internal motions, with comparisons having been made against crystallographic B-factors and NMR conformational variabilities. ENMs have become an increasingly important tool and have been widely used to comprehend protein dynamics, function, and even conformational changes. However, reliance upon an arbitrary cutoff distance to delimit the range of interactions has p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
285
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(303 citation statements)
references
References 57 publications
(69 reference statements)
17
285
1
Order By: Relevance
“…4. This result is a close match to the findings of Yang et al 67 and their parameter free ENM (pfENM) model. In the pfENM, spring constants are scaled by an inverse power.…”
Section: B Fri Based B-factor Predictionsupporting
confidence: 81%
See 2 more Smart Citations
“…4. This result is a close match to the findings of Yang et al 67 and their parameter free ENM (pfENM) model. In the pfENM, spring constants are scaled by an inverse power.…”
Section: B Fri Based B-factor Predictionsupporting
confidence: 81%
“…In the pfENM, spring constants are scaled by an inverse power. Yang et al 67 tested powers 1-10 and found second and third inverse power relationships were the most accurate for B-factor predictions. 67 In our study, we also test noninteger powers over the range 0.5-10.0 and come to a similar conclusion.…”
Section: B Fri Based B-factor Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] This approach, which attempts to predict fluctuations and dynamics from a single protein structure, is not directly comparable to the LE4PD model we present here, where we model the dynamics and take the structural ensemble from experiment or by sampling an underlying atomistic model via MD simulation. Like other elastic network models [7][8][9][10][11] the coupled rotator model is capable of capturing the local variation in flexibility along the protein chain with no site-specific adjustable parameters, but because it begins from an empirical network description it requires a large amount of parameterization and specification of an overall rotational diffusion time τ 0 , a scaling factor k 0 , a cut-off distance R c , and a characteristic internal diffusion time t D . The model is explicitly limited to small displacements around a single conformational minima, and relaxation times centered upon a short characteristic internal diffusion time of ∼ 300ps.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Other theoretical models based upon effective harmonic descriptions, which calculate sequence dependent protein flexibility, are Normal Mode Analysis (NMA), and general Elastic Network Models (ENM) including the Gaussian Network Model (GNM). [12][13][14][15][16] Differently than the LE4PD, those models were designed to study short-time vibrational fluctuations around the protein structure, which are dominated by the topology of native contacts. Because the LE4PD is a diffusive equation of motion which contains information about the extent of the intramolecular energy barriers, specific monomer friction coefficient, amino-acid specific local semiflexibility, degree of hydrophobicity, as well as hydrodynamics, it provides a realistic description of the motion of proteins in solution over a wide range of timescales, from the local vibrational fluctuations as measured by crystallographic B-factors, to the long-time dissi-pative dynamics.…”
Section: Introductionmentioning
confidence: 99%